Gen Zersâ€™ Stances on The Religion Role in Human Salvation - Sugiarto, Bernardus Ario Tejo; Kahmad, Dadang; Huriani, Yeni (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2022)
Each generation has its character because of the differences in era context. The Z Generation (Gen Zers) also has distinctive features that are different from the previous generation. Gen Zers is a generation that lives in the context of the world that is strongly influenced by scientific and digital technological advances in all fields, especially in communication and information fields. In Western countries, there are serious symptoms of a decline in the number of Gen Zers who are affiliated with a religion or who attended Church. They think that being affiliated with a religion or attending Church isnâ€™t something very important. Yet, it doesnâ€™t mean that they disregard the values of spirituality and morality. On the contrary, they are deeply concerned with universal spiritual and moral values. For them, spirituality and morality are â€œyesâ€, but religion is â€œnoâ€. The studyâ€™s purpose is to investigate the role of religion according to Gen Zersâ€™ opinions in Bandung. The study method is a quantitative method that makes use of an e-questionnaire as a data collection tool. All respondents are students who are studying at a certain private university in Bandung. The main finding is almost all respondents opine that affiliating with religion isnâ€™t determining factor for human salvation even though they are affiliated with a religion. The conclusion is that there are at least five ambiguous stances of Gen Zers on the role of religion in human salvation. They are religious formalism, agnosticism, religious indifferentism, practical atheism, and religionism.